HUBUNGAN PENGETAHUAN PERAN TENAGA KESEHATAN TEKNIK MENYUSUI TERHADAP KEJADIAN BENDUNGAN ASI PADA IBU MENYUSUI DI PMB BD N TAHUN 2023 - Pratami, Siti Shepia; Yolanda, Rita Ayu; K, Millka Anggraeni (SINERGI : Jurnal Riset Ilmiah, 2025)
Breast engorgement is one of the common problems experienced by breastfeeding mothers, caused by improper breastfeeding techniques, lack of maternal knowledge, and suboptimal roles of health workers in providing education. This condition can lead to pain, swelling, and even breast infection if not properly managed. This study aimed to determine the relationship between knowledge, the role of health workers, and breastfeeding techniques with the incidence of breast engorgement among breastfeeding mothers at PMB BD N, Cisarua District, Bogor Regency, in 2023.This research used a quantitative approach with a quasi-experimental design, specifically a two-group post-test only design. The total sample was 30 respondents consisting of 15 intervention respondents and 15 control respondents, selected using purposive sampling. Data were collected using questionnaires and analyzed using univariate and bivariate analysis with the Mann-Whitney test. The results showed a significant relationship between knowledge and breast engorgement (p = 0.004), the role of health workers and breast engorgement (p = 0.003), and breastfeeding technique and breast engorgement (p = 0.000).           There is a significant relationship between knowledge, the role of health workers, and breastfeeding techniques with the incidence of breast engorgement among breastfeeding mothers